Penerapan Digital Marketing pada UMKM Dodol Hawa Desa Pakning Asal Kabupaten Bengkalis - Putri Desika Sari; Dwi Astuti (Politeknik Kampar, 2025)
This final project is carried out to find out how the application of digital marketing promotes products at MSME Dodol Hawa located in Pakning Asal Village, Bengkalis Regency. The main objective of this project is to assist businesses in expanding market reach and increasing product attractiveness through digital media. The methods used are Strenght, Weaknesess, Opportunity, Threats (SWOT) analysis, and Segmenting, Targeting, Positioning (STP). The digital marketing strategy implemented includes the use of social media (Instagram, Facebook Business, and WhatsApp Business), the creation of a Google My Business account, and the utilization of the Facebook marketplace. The project results show that the use of social media plays an important role in increasing brand awareness and consumer interest. However, there are still obstacles such as the lack of understanding of technology from business actors and limited ideas in creating attractive digital content. The solution is that continuous mentoring and training are needed so that digital marketing strategies can be implemented optimally, have a long-term impact on business sustainability and continuously seek reference ideas from various sources to get interesting content ideas.